2011
DOI: 10.1103/physrevlett.106.097001
|View full text |Cite
|
Sign up to set email alerts
|

Are “Pinholes” the Cause of Excess Current in Superconducting Tunnel Junctions? A Study of Andreev Current in Highly Resistive Junctions

Abstract: In highly resistive superconducting tunnel junctions, excess subgap current is usually observed and is often attributed to microscopic pinholes in the tunnel barrier. We have studied the subgap current in superconductor-insulator-superconductor (SIS) and superconductor-insulator-normal-metal (SIN) junctions. In Al/AlO(x)/Al junctions, we observed a decrease of 2 orders of magnitude in the current upon the transition from the SIS to the SIN regime, where it then matched theory. In Al/AlO(x)/Cu junctions, we als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
45
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 33 publications
7
45
1
1
Order By: Relevance
“…3(b) indicates 3 pA, which we have chosen as a biasing current for the temperature probe. This value is in the temperature sensitive region, not influenced by the Andreev current leakage [30][31][32] that appears as a constant slope at low bias values in Fig. 3(b).…”
mentioning
confidence: 90%
“…3(b) indicates 3 pA, which we have chosen as a biasing current for the temperature probe. This value is in the temperature sensitive region, not influenced by the Andreev current leakage [30][31][32] that appears as a constant slope at low bias values in Fig. 3(b).…”
mentioning
confidence: 90%
“…Structural defects at the interface [3,5], roughness of the metal substrate [4,10,11] and nonuniformity of the oxide thickness [3,7,8] are anticipated to be the critical factors, which may deteriorate the functionality of the oxide as a barrier. However, characterization of this impact is in its early stage and hence still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…7 Subgap conductance of defect-free NIS junctions is dominated by two-particle Andreev tunneling. 8 For n qp , studies on superconducting qubits 2,3 and resonators 5 have reported a low-temperature saturation to 10-55 μm −3 due to an unidentified excitation mechanism. Recently, a significantly improved result n qp < 1 μm −3 has been obtained by a transmon qubit realization.…”
Section: Introductionmentioning
confidence: 99%